Maturity of Student Career Planning in MAN 1 Agam - Zetrizal Zetrizal; Netrawati Netrawati (Jurnal Neo Konseling, 2021)
Career planning maturity is a process where individuals are able to know and understand themselves well, have knowledge of the desired career world, and are able to integrate information themselves with existing jobs or further education. This study aims to describe the career planning maturity of MAN 1 Agam students in terms of: 1) Describing the maturity of the career planning of MAN students from all aspects 2) Describing the maturity of the career planning of MAN students based on aspects of knowledge and understanding of themselves. 3) Describe the maturity of MAN student career planning based on aspects of knowledge and understanding of work. 4) Describe the maturity of MAN student career planning based on the aspect of integrating self-information with existing jobs. This type of research is a quantitative descriptive study. The samples of this research were students of MAN 1 Agam which consisted of class X to class XII. The research sample consisted of 173 students based on the proportional random sampling technique. The research was conducted by administering a questionnaire on the maturity of students' career planning. The data were processed using descriptive statistical analysis techniques. The findings of this study describe the maturity results of the career planning of MAN 1 Agam students in the mature enough category.